Diseño de un mecanismo para el mejoramiento de la calidad y el posicionamiento de marca de la microempresa de agua Aguantisana en la ciudad de Quito - Rodríguez Tuitise, Karla Estefanía (2015)
This project is focused on improving sales AGUANTISANA microenterprise, located in the city of Quito, dedicated to purification and distribution of water bottle, for which a study of the history of it that is done to obtain data Historic help to generate a proposal to improve the process of production ( quality), marketing and communication management (positioning). Therefore the market study allows to know the conditions of this and customer behavior microenterprise, in turn, provides an overview of companies that are open to consume water bottle and the price you are willing to pay, generating information that promotes the new design of effective strategies for increasing market share microenterprise. As for the design of the technical study propose a new process of marketing and distribution that offers microenterprise for this use if so provided within this increased value-added services for direct clients, as well as a direct marketing strategy using a distribution channel of second level to enterprise customers. Within the study and financial evaluation concludes that if the proposed strategies are applied, micro maintain its benefit over cost, and increase your sales will improve their image with current and potential customers, which will allow it to continue to grow over time.